PELATIHAN ERGONOMI ANGKAT ANGKUT DAN PENILAIAN ERGONOMITAS PADA PORTER PELABUHAN SAMARINDA - Rachmawati, Eka; Parengkuan, Sandra Reinny; Aditya, Aditya; Kartinah, Kartinah; Nursafa, Andi; Rohmah, Nur; Nurrachmawati, Annisa (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Port porters are at high risk of occupational accidents and musculoskeletal disorders due to the use of non-ergonomic lifting and carrying techniques. Complaints such as pain in the back, neck, shoulders, and other body parts are common problems among stevedoring workers. This activity aims to improve the capacity of port porters through ergonomic evaluation, education, and training so they can work safely and more productively. The approach used is community empowerment with the Community Based Participatory Research (CBPR) method, which includes five stages: problem identification, priority setting, program design, outcome evaluation, and follow-up. The results of the activity showed a significant increase in porter knowledge at Samarinda Port, although some participants still do not apply correct lifting techniques in the field. It is hoped that ongoing socialization activities can be carried out by trained porters to colleagues who have not received training, so that this program can be sustainable and have an impact on improving safety and work productivity.